The interplay of legal and social norms and the failure of the bank credit market in Bulgaria - Ingrid Größl (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2005)
We take up the widely held view that the observed discrepancy between law on the books and law in action has prevented economic transition and investigate its role for the failure of the Bulgarian credit market. In doing so, we focus on the role of injunctive informal institutions which have become internalized in the course of social development. Based on cross-cultural psychology, we show that a particular bundle of fundamental social norms which constitute basic value orientations have both prevented the development of stabilizing regulations and an overall compliance with prevailing laws.
Keywords: G21; G38; P14; P21; P31; P39; Z00; 330